Proceedings of the 1st Kültepe International Meeting, Kültepe, 19-23 September, 2013 (Turnhout)
xiv, 249 s.
Keywords: "This first volume of the Kültepe International Meetings gathers interdisciplinary studies dedicated to Kültepe, ancient Kaneš (central Anatolia), and its environment, mainly during the Bronze Age. This book is the first of a new series dedicated to the site of Kültepe, ancient Kaneš, in central Anatolia. It is the report of a conference which took place at Kültepe on September 2013. Contributions written by the best specialists of the field focus on Kültepe and its environment, mainly during the Bronze Age, and on its Assyrian settlement located in the lower town. The volume brings about a reflection on archaeological and textual materials, and provides an interdisciplinary summary of the state of research. It is divided into six sections dedicated to the following topics: archaeology, chronology and population of Kültepe; archives unearthed in the houses belonging to Assyrians; Old Assyrian writing and literacy; Anatolian settlements and daily life; metals and minerals; Kültepe after the Middle Bronze Age." --